A bibliography of Meiteiron (Manipuri) linguistics - Chelliah, Shobhana L. (2024)
This bibliography is a listing of published and unpublished books, dissertations, and articles on the Tibeto-Burman language Metteiron (also known as Manipur' or Meitei, spoken primarily in the state of Manipur, in Northeast India). I have indicated in parentheses after each listing, that I have the item (H): or that I have the item and have had it translated from Meiteiron to English (H:Trans): or that I have seen the item in Manipur University but have not acquired it (S:MU): or that I have looked for the item and have determined that it is no longer available (NA); or that I have not yet acquired or seen the item (NYA).